1994
DOI: 10.1111/j.1476-5381.1994.tb17165.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable potency of nitrergic‐nitrovasodilator relaxations of the mouse anococcygeus against different forms of induced tone

Abstract: during Ca2' re-loading, increased the subsequent residual contraction to carbachol in Ca2+-free medium.7 At higher concentrations, SNP (0.1-10 fM) produced a partial relaxation of the sustained contraction to U46619 in Ca2+-free medium. 8 Thus, the relaxant potency of the nitrergic stimuli was dependent on the agent and mechanism used to induce tone in the preparation. Examination of the contractile/relaxant interactions suggests that altered Ca2+ sequestration and inhibition of contractile protein function ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…We have previously shown that CPA-induced contractions of the whole muscle, whilst being largely unaffected by nifedipine (1 giM), are inhibited by SKF 96365, (pIC50 approximately 6.4; Gibson et al, 1994). In the present series of experiments, we extended these observations by testing the ability of several divalent and trivalent cations to inhibit the CPA-induced contractions.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…We have previously shown that CPA-induced contractions of the whole muscle, whilst being largely unaffected by nifedipine (1 giM), are inhibited by SKF 96365, (pIC50 approximately 6.4; Gibson et al, 1994). In the present series of experiments, we extended these observations by testing the ability of several divalent and trivalent cations to inhibit the CPA-induced contractions.…”
Section: Resultssupporting
confidence: 55%
“…Second the current was blocked by the chloride channel blockers, DIDS and A-9-C, both of which have been shown to block calcium-dependent chloride currents in other smooth muscles (Baron et al, 1991;Wang et al, 1992). Third, the current-voltage relationship for the current showed marked outward rectification similar to that of the calcium-dependent chloride current first described in smooth muscle cells isolated from the rat anococcygeus (Byrne & Large, 1987 (Gibson et al, 1994).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations